PENGEMBANGAN MEDIA PEMBELAJARAN AUGMENTED REALITY PADA MATERI “INI KHAS DAERAHKU” UNTUK MENINGKATKAN HASIL DAN MINAT BELAJAR IPAS KELAS IV SD - Galuh Nawang Wulan; Tri Astuti (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
ABSTRACT The acceleration of digital technology in the education sector has significantly enhanced the integration of interactive learning media; however, elementary schools are still dominated by conventional media, and previous research has not extensively examined both student interest and learning outcomes simultaneously in the context of augmented reality. Therefore, this study is important to address this gap. This research focuses on the development of augmented reality learning media through the Assemblr Edu platform, which has met the criteria for validity and effectiveness in optimizing student learning outcomes and motivation in the IPAS subject “Ini Khas Daerahku” for fourth-grade students at SDN 1 Jati. The development of learning media in this study adopts a Research and Development (R&D) approach by implementing the 4D stages, which include definition, design, development, and dissemination. Data collection was conducted using pretest-posttest instruments, questionnaires, interviews, observations, and documentation, with data analysis techniques including normality tests, t-tests, and n-gain. Based on the validation test results, the media was deemed highly suitable for use after receiving a 87.5% rating from subject matter experts and 96% from media experts, with an overall average of 91.75%. Findings from the effectiveness test indicated that a significant improvement in performance occurred, with a pretest average score of 46.50 and a posttest average score of 86.75, as well as an N-gain of 0.76, which falls into the high category. This data indicates that the use of assemblr.edu-based augmented reality media is not only valid and effective in improving students' understanding of the material